2015
DOI: 10.1515/eb-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Passengers’ Satisfaction at “RIGA International Airport”

Abstract: The aim of the paper is to determine complex factors influencing passengers' satisfaction at RIGA International Airport (Latvia). Theoretical evidence was examined and factor analysis was carried out to identify the main groups of factors affecting passengers' satisfaction at the Airport. The findings of the study show that the most important five factors affecting it are: (1) availability of telecommunications, (2) effective way finding signs, (3) cleanliness of restrooms, (4) courtesy of staff and (5) availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Therefore, the most critical step in defining and delivering high-quality service is to understand what passengers expect. Meeting or exceeding passenger expectations results in passenger satisfaction with the services offered by the airport [23]. Passenger satisfaction strengthens customer loyalty and purchase intention while improving airport operators' overall business performance [24].…”
Section: Literature Review and Hypotheses Formulation 21 Airport Serv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the most critical step in defining and delivering high-quality service is to understand what passengers expect. Meeting or exceeding passenger expectations results in passenger satisfaction with the services offered by the airport [23]. Passenger satisfaction strengthens customer loyalty and purchase intention while improving airport operators' overall business performance [24].…”
Section: Literature Review and Hypotheses Formulation 21 Airport Serv...mentioning
confidence: 99%
“…In addition, Mirghafoor et al [31] asserted that airport staff is critical in service quality. Furthermore, Paramonovs and Ijevleva [23] emphasized the importance of airport staff courtesy and competence in determining customer satisfaction or dissatisfaction. The above literature led to the following hypothesis: Hypothesis 8 (H8).…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Customer surveys have been widely used to evaluate airport customer satisfaction and service quality. A large number of studies have investigated the importance of airport service quality by conducting surveys and suggested possible improvement proposals (Allen et al 2020a(Allen et al , 2020b(Allen et al , 2021Bellizzi et al 2018;Ceccato and Masci 2017;Brida et al 2016;Pandey 2016;Gomes 2015, 2016;Paramonovs and Ijevleva 2015;Jeon and Kim 2012;Liou et al 2011). For example, Allen et al (2021) investigated airport passengers' satisfaction to create practical strategies for airport services.…”
Section: Traditional Customer Satisfaction Surveys and Interviewsmentioning
confidence: 99%
“…Bellizzi et al (2018) conducted face-to-face interviews to evaluate passengers' satisfaction toward the Lamezia Terme airport's service quality and revealed that satisfaction factors and levels differ depending on travelers' backgrounds. Paramonovs and Ijevleva (2015) also employed a survey method to analyze major satisfaction factors for passengers at Riga International Airport in Latvia. Using 937 valid samples, the results indicated that telecommunications, effective signage, clean restrooms, staff courtesy, and availability are key factors affecting air passengers' satisfaction.…”
Section: Traditional Customer Satisfaction Surveys and Interviewsmentioning
confidence: 99%
“…Terminal cleanliness has long been a concern for passengers, impacting tolerance for lapses [18]. Research supports that terminal cleanliness positively influences passengers' emotions and overall satisfaction [8,15,17,45,46]. Travelers arriving early prioritize cleanliness, while foreign passengers emphasize information displays [47].…”
Section: Hypothesis Developmentmentioning
confidence: 99%